THE USE OF VISUAL AIDS IN THE TEACHING OF ACCOUNTING. - Thompson, David W. (The Accounting Review, 1948)
Abstract The teaching of accounting represents one of the most formidable challenges to the adapting of visual aids to teaching situations. This is true because of the very nature of accounting. Accounting requires some abstract thinking, especially in advanced courses. Abstractions are very difficult to visualize. Accounting requires the study of detailed forms and statements, and, until recently, projection devices have not been of adequate power to project these necessary details. This explains in part the slight use of visual aids in accounting instruction. Another explanation is that accounting instructors are not aware of the possibilities of visual aids and arc not trained in their use. However, since tests show that an individual learns primarily through his sense of sight, it seems that efforts should be made to use visual aids in teaching accounting in spite of the difficulties encountered. Some of the visual aids are, The blackboard, motion pictures, lantern slides, filmstrips, charts plant visits, and others. Visual aids are only an aid or supplement to the instructor. They cannot replace a text or instructor or outside study on the part of the Student. The use of visual aids will not lessen the work of the instructor. The instructor will work more, but he will work more effectively. If properly used they will result in more thorough coverage of the material presented.